Pengaruh kenyamanan dan periklanan terhadap perilaku konsumen yang di moderasi oleh kepercayaan - Laura, Netty; Safitri, Nisa Nur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of advertising and advertising on consumer behavior which is moderated by trust. The population in this study are Indonesian e-commerce customers. The sampling technique used the Random Sampling method. The number of data is 100 respondents who are taken through a questionnaire using partial least squares (PLS) data analysis. Based on statistical tests, the results obtained from this study, firstly, convenience does not have a significant effect on consumer behavior, which means that based on this the hypothesis in this study is rejected. Second, advertising has a significant effect on consumer behavior, which means that based on this the hypothesis in this study is accepted. Third, trust has no significant effect on consumer behavior, based on this the hypothesis in this study was rejected. Fourth, trust cannot moderate the comfort of consumer behavior based on this hypothesis 4 in this study is rejected. Fifth, trust can moderate advertising on consumer behavior based n this hypothesis 5 in this study is accepted.